Respiration of bivalves from three different deep-sea areas: Cold seeps, hydrothermal vents and organic carbon-rich sediments. (August 2017) - Khripounoff, A.; Caprais, J.C.; Decker, C.; Le Bruchec, J.; Noel, P.; Husson, B.
Abstract: We studied bivalves (vesicomyids and mytilids) inhabiting four different areas of high sulfide and methane production: (1) in the Gulf of Guinea, two pockmarks (650 m and 3150 m depth) and one site rich in organic sediments in the deepest zone (4950 m average depth), (2) at the Azores Triple Junction on the Mid-Atlantic Ridge, one hydrothermal site (Lucky Strike vent field, 1700 m depth). Two types of Calmar benthic chambers were deployed, either directly set into the sediment (standard Calmar chamber) or fitted with a tank to isolate organisms from the sediment (modified Calmar chamber), to assess gas and solute exchanges in relation to bivalve bed metabolism. Fluxes of oxygen, total carbon dioxide, ammonium and methane were measured. At the site with organic-rich sediments, oxygen consumption by clams measured in situ with the standard benthic chamber was variable (1.3–6.7 mmol m −2 h −1 ) as was total carbon dioxide production (1–9.6 mmol m −2 h −1 ). The observed gas and solute fluxes were attributed primarily to bivalve respiration (vesicomyids or mytilids), but microbial and geochemical processes in the sediment may be also responsible for some of variations in the deepest stations. The respiration rate of isolated vesicomyids (16.1–0.25.7 µmol g −1 dry weight h −1 ) was always lower than that of mytilids (33 µmol g −1 dry weight h −1 ). This difference was attributed to the presence of a commensal scaleworm in the mytilids. The respiratory coefficient (QR) ≥1 indicated high levels of anaerobic metabolism. The O:N index ranged from 5 to 25, confirming that vesicomyids and mytilids, living in symbiosis with bacteria, have a protein-based food diet.